Calibration of an in-situ fluorescence-based sensor platform for reliable BOD5 measurement in wastewater - K. Khamis (IWA Publishing, 2021)
Reliance on biochemical oxygen demand (BOD5) as an indicator of wastewater quality has hindered the development of efficient process control due to the associated uncertainty and lag-times. Surrogate measurements have been proposed, with fluorescence spectroscopy a promising technique. Yet, assessment of in-situ fluorescence sensors across multiple wastewater treatment plants (WwTPs), and at different treatment stages, is limited. In this study a multi-parameter sonde (two fluorescence peaks, turbidity, temperature and electrical conductivity) was used to provide a BOD5 surrogate measurement. The sonde was deployed at three WwTPs, on post primary settlement tanks (PST) and final effluent (FE). Triplicate laboratory measurements of BOD5, from independent laboratories were used to calibrate the sensor, with high variability apparent for FE samples. Site and process specific sensor calibrations yielded the best results (R2cv = 0.76–0.86; 10-fold cross-validation) and mean BOD5 of the three laboratory measurements improved FE calibration. When combining PST sites a reasonable calibration was still achieved (R2cv = 0.67) suggesting transfer of sensors between WwTPs may be possible. This study highlights the potential to use online optical sensors as robust BOD5 surrogates in WwTPs. However, careful calibration (i.e. replicated BOD5 measurements) is required for FE as laboratory measurements can be associated with high uncertainty. HIGHLIGHTS A sensor calibration procedure for BOD5 measurement was assessed at three wastewater treatment plants (WwTPs).; Calibration for final effluent required replicated BOD5 sampling to reduce uncertainty.; Calibration for post settlement was robust and suggested sensor transfer between WwTPs is possible.; Robust calibration for in-situ BOD5 monitoring can improve process control and reduce pollution events.;